Par-delà le naturalisme : médiatisation du sublime dans les oeuvres d’Olafur Eliasson et Ryoji Ikeda - Ouellet, Maryse (RACAR : Revue d'art canadienne / Canadian Art Review, 2016)
Although the sublime is commonly associated with nature, the historical determinants of this relation are frequently ignored. Art historians and curators who attempt to define a contemporary sublime often anachronistically link recent artworks with modern categories marked by a now contested representation of the world. Such is the case of the “natural sublime,” which emerged around the turn of the eighteenth century and exemplifies what Philippe Descola describes as a “naturalistic” cosmology characterized by a separation between Nature and Culture. Starting from a case study of two recent art installations associated with the sublime, namely The weather project (2003) by Olafur Eliasson and the series systematics and datamatics (2012) by Ryoji Ikeda, this article examines how these works reconfigure the relation between the subject and the world, in order to characterize the contemporaneity of their representation of the sublime. It suggests that these installations help reformulate our interpretation of it by emphasizing the power of technological and digital mediations to connect the human and the non-human worlds.